2014
DOI: 10.1142/s0218625x14300020
|View full text |Cite
|
Sign up to set email alerts
|

REVIEW ON ELECTROLESS PLATING NiP COATINGS FOR IMPROVING SURFACE PERFORMANCE OF STEEL

Abstract: Electroless plating has been considered as an effective approach to provide protection and enhancement for metallic materials with many excellent properties in engineering field. This paper begins with a brief introduction of the fundamental aspects underlying the technological principles and conventional process of electroless nickel–phosphorus ( Ni – P ) coatings. Then this paper discusses different electroless nickel plating, including binary plating, ternary composite plating and nickel plating with nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 64 publications
0
24
0
3
Order By: Relevance
“…21 This is consistent with other research results. 10,21,22 The full width at half maximum (FWHM) of the peak became narrower when the temperature increased. The results indicated that the higher bath pH would facilitate the formation of larger average grain size and enhance the crystallinity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 This is consistent with other research results. 10,21,22 The full width at half maximum (FWHM) of the peak became narrower when the temperature increased. The results indicated that the higher bath pH would facilitate the formation of larger average grain size and enhance the crystallinity.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] The catalysts (such as Au, Ag and Pd) is key to the subsequent successful electroless plating result from the ones serve as seeds to catalyze the electroless plating on polymer surface. 10,11 Lots of research for modifying the polymer surface were reported including plasma treatment, 12 exposure to°a mes wet-chemical pretreatment, 13 and photoetching. 14 Domenech et al 15 reported that the electroless Ni-P plating on poly (ethylene terephthalate) (PET) substrates were treated by acid etching.…”
Section: Introductionmentioning
confidence: 99%
“…Electroless plating is a chemical reduction of a metallic ion in a solution containing a reducing agent, and the ensuing deposition of the metal without electrical energy [92]. The incorporation of TiO 2 nanoparticles into the electroless plated Ni-P matrix has been identified as a means of increasing the hardness, corrosion resistance [93] and wear resistance of the coating [94].…”
Section: Electroless Platingmentioning
confidence: 99%
“…Coatings are widely used for corrosion protection [23]. However, there are no reports on H 2 S resistant coating in open literature.…”
Section: International Journal Of Materials Mechanics and Manufacturmentioning
confidence: 99%
“…All these would lead to failure of the liners and causes serious negative impact on production, which includes, but are not limited to, reduced bitumen production, poor sand control performances and lower quality of bitumen product (with considerable amounts of fine solids that further leads to difficulties in oil/solid/water separation and water treatment and recycling in SAGD operations). Coatings are widely used for corrosion protection [23], however, there are no reports on H2S resistant coating in open literature. This work proposes an integrated research program that intends to identify effective and scientifically validated tools for use in the in-situ recovery of heavy oil by thermally and chemically enhanced means.…”
Section: Introductionmentioning
confidence: 99%